EVALUATION OF HYBRID LEARNING IMPLEMENTATION OF AVIATION ENGLISH LEARNING IN VOCATIONAL HIGHER EDUCATION - Octavianie, Adhitya; Syamsuriani, Syamsuriani; Rossydi, Ahmad (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Politeknik Penerbangan Makassar has recently used hybrid learning for the first time, following the Ministry of Transportation's adoption of this approach in response to the Covid-19 outbreak. The objective of this study was to assess the implementation of Hybrid Learning in the English Course for Air Traffic cadets at Politeknik Penerbangan Makassar, with a focus on the comprehension and administration of Hybrid Learning by instructors, as well as the cadets' understanding of Hybrid Learning. The research employed quantitative research methods. The present study used the CIPP (Context, Input, Process, Product) evaluation paradigm as a questionnaire item administered to lecturers and cadets. The findings indicated that the lecturers achieved high marks in their comprehension and handling of Hybrid Learning, as assessed through the CIPP examination. The calculation results indicate the following percentages for each element: (1) Context aspect with 75.65%, (2) Input aspect with 84.92%, (3) Process aspect with 80.22%, and (4) Product aspect with 66.5%. In the interim, the results achieved by cadets in relation to their comprehension and handling of Hybrid Learning, as assessed by the CIPP evaluation, fell within the high range. The computation results of each facet are evident from the data presented. The results indicate that the context aspect received a score of 84.67%, the input aspect received a score of 82.08%, the process aspect received a score of 81.67%, and the product aspect received a score of 79.19%. In general, the lecturers demonstrated a good level of understanding and proficiency in managing Hybrid Learning, with a score of 76.82%. Similarly, the cadets exhibited a high level of understanding and proficiency in their management of Hybrid Learning, with a score of 81.90%.